Hedonic Value in Customer Satisfaction: A Bibliometric Analysis - Radina Noorsahadita; Lissa Rosdiana Noer (Dinasti Publisher, 2025)
This study systematically maps research on hedonic value and customer satisfaction using a bibliometric approach, in order to identify dominant themes, research gaps, and key contributions in the field. Bibliometric analysis was conducted using the Scopus database, focusing on articles discussing